Lithological Controls on Acid Mine Drainage Formation: An Integrated Rock Characterization of AMD Sources in the Sungai Seluang Area, East Kalimantan, Indonesia - Jamaluddin; Muhammad Syifaul Qulub; Nijusiho Manik; Emi Prasetyawati Umar; Hamriani Ryka; Efrina Chandra Agusti Putri (International Journal of Hydrological and Environmental for Sustainability, 2026)
Acid Mine Drainage (AMD) represents a critical environmental challenge in coal-mining regions, particularly due to its long-term impacts on surface water quality and surrounding ecosystems. This study investigates the lithological controls on AMD formation in the Sungai Seluang area, East Kalimantan, Indonesia, through an integrated rock characterization approach. The novelty of this research lies in linking detailed lithological attributes and pyrite micro-morphology with AMD generation potential and its implications for riverine water systems. Macroscopic lithological observations were combined with standardized pH testing (SNI 6989.11:2019) and Scanning Electron Microscopy (SEM) to evaluate the acid-generation characteristics of representative rock units. The results indicate that 92% of the analyzed samples are classified as Potentially Acid Forming (PAF), while only 8% are Non-Acid Forming (NAF). The study area is lithologically dominated by claystone (42%), sandstone (31%), and shale (27%), all of which commonly exhibit intense oxidative staining, pervasive fracturing, and weathering features that significantly enhance sulfide exposure to oxygen and water. SEM analyses reveal the presence of both euhedral and framboidal pyrite, with framboidal pyrite identified as particularly reactive and influential in accelerating acid production. Measured pH values are predominantly acidic (<6), indicating a high AMD potential that poses a serious threat to the Sungai Seluang system through acidification and metal mobilization. These findings demonstrate that lithology and micro-scale mineralogical characteristics play a decisive role in controlling AMD formation and its environmental consequences. The integrated approach adopted in this study provides a robust framework for early AMD source identification and supports the development of more effective geochemical management strategies aimed at protecting water quality and minimizing long-term environmental degradation in coal-mining areas.